Design and Virtualization of an Automated System with Hardware in the Loop for the Virtualized Water Bottling Process in a Unity Environment - Pico, Lucía (2023)
This article presents the design and virtualization of a water bottle packing plant in the Unity software, with the implementation of an automated system with human-machine interface - supervision, control and data acquisition (HMI) for the water bottling process, where, through the use of SolidWorks software, the bottling plant was created and exported to an fbx file so that it can be read by Unity, so that, through the Logo Soft software, the inputs and outputs of the plant can be programmed and this is controlled through the use of a Siemens Logo using the Modbus network as the open communication protocol to obtain the operation of a bottling plant in the industry in a virtual scenario, this being an easy to operate module of low cost where master information will be provided to the computer to send the slave, which will be the Arduino together with the PLC, resulting in a friendly, intuitive and realistic environment of a water bottling plant, in addition to presenting an alternative for students and industries in order to have an interaction with the plant, know its operation and possible failures that it would have without the need for an economic or unnecessary expense.